Do you really miss out if you are missing out? Students’ everyday and workplace FOMO phenomenon in relation to social media addiction at three Hungarian universities - Kővári, Edit; Hargitai, Dávid; Liska, Fanny (Vezetéstudomány / Budapest Management Review, 2023)
FOMO (Fear of Missing Out) refers to users’ fear of not being able to see online content and people’s interactions, react to them in a timely manner and not participating in live activities. FOMO can lead to anxiety, sleep disorders, lack of concentration and chronic dependence on social media. A „counter-trend” also seems to have emerged: Joy of Missing Out (JOMO) is a feeling that develops during vacations, trips to nature, eating and strong focus. This research examines the dynamics of the FOMO-JOMO phenomenon and how it develops, user attitudes, and its consequences. The results of the literature correlation study are illustrated by a correlation visualisation applying the Web of Science database. Multivariate analysis techniques were used to investigate the four hypotheses. Two FOMO factors were identified: the comparison to others (online) and the missing out experience (offline). Regarding workplace FOMO, two factors emerged: relationship exclusion and information exclusion.